ANALISIS IMPLEMENTASI SISTEM EVAKUASI PASIEN DALAM TANGGAP DARURAT BENCANA KEBAKARAN PADA GEDUNG BERTINGKAT DI RUMAH SAKIT X SEMARANG - Octa Hermanto; Baju Widjasena; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Hospital as one of the health facilities that provide health services to the community, has the potential fire disaster. Hospital has emergency response planning evacuation systems exist when a disaster occurs. Evacuation system in different hospitals with more general multi-storey buildings. Hospital X has a patient care building with 7 floors and a capacity of 450 patients. This study was to analyze the patient evacuation system for emergency response of fire in multi-storey buildings in the hospital. This research is a descriptive Qualitative in-depth interviews. The subjects of this study consists of 4 people as the main informants and the first person to informant triangulation. The results show management has established policies and commitment to patient evacuation system it is shown by the Standard Operational Services on the evacuation of patients in the multi-storey building, but the Standard Operational Services is not yet known by the public. providing training for human resources at the hospital, human resource capacity is not adequate for emergency response and evacuation means are minimal. What is needed is a means of evacuation stretchers, ramp and lifts to fire. Budgeting system is with the submission of a business plan the budget, to great expense to do priority. hospital have a communication system during an emergency to announce and request assistance to help during emergency. Hospital X needs to review existing procedures and have an innovation to the possibility of additional procedures for the evacuation of patients with limited means. Develpo the quality of training for human resources preparedness